2019
DOI: 10.21614/chirurgia.114.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Malignant Intestinal Obstruction: Outcome and Prognostic Factors

Abstract: Context: Ocluzia intestinală de cauză malignă este o complicaţie frecventă la pacienţii cu cancer în stadii avansate. Prognosticul este slab, cu o rată medie de supravieţuire mai mică de 3 luni. Tratamentul clinic, procedurile endoscopice sau chirurgicale sunt opţiuni pentru managementul obstrucţiei intestinale maligne. Nu există o strategie de management general acceptată. Obiective: Evaluarea factorilor de prognostic ai pacienţilor cu obstrucţie intestinală malignă care au fost supuşi unui tratament chirurgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Intestinal obstruction is a clinical multiple acute abdomen disease with a mortality rate of about 5%-10%. Previous studies have shown that intestinal obstruction can not only cause physical harm but also lead to psychological problems such as depression and anxiety [ 11 , 12 ]. Furthermore, those who lack correct recognition of intestinal obstruction lack confidence in the treatment of the disease, and the above psychological problems are more prominent [ 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal obstruction is a clinical multiple acute abdomen disease with a mortality rate of about 5%-10%. Previous studies have shown that intestinal obstruction can not only cause physical harm but also lead to psychological problems such as depression and anxiety [ 11 , 12 ]. Furthermore, those who lack correct recognition of intestinal obstruction lack confidence in the treatment of the disease, and the above psychological problems are more prominent [ 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study, Daniel P Park et al [13] analyzed 7227 postoperative esophageal cancer patients in England, Wales and Northern Ireland from 1995 to 2007 and found that postoperative serum albumin levels were an important predictor of mortality risk. Jorge Henrique Bento de Sousa et al [20] found that hypoalbuminemia in patients with postoperative intestinal obstruction was often associated with high postoperative mortality. Studies have found [21] that hypoalbuminemia is an important factor affecting the prognosis of patients with pneumonia, patients after esophageal cancer surgery, and patients after major abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] It is defined as the evidence of bowel obstruction distal to the Treitz ligament in the presence of a primarily intra or extra abdominal neoplasm with peritoneal dissemination. 4 Patients presenting MBO possibilities include resections, stomas or bypasses. 1,5 Few studies have compared the efficiency of these management modalities and there are no guidelines on MBO.…”
Section: Introductionmentioning
confidence: 99%